Avaliação das ações de acessibilidade propostas no Plano Diretor de Goiânia (Lei Nº 171/2007) - Dias, Wesley Afonso da Silva (2019)
The actions towards urban mobility involve many factors, as the elaboration of a plan for urban mobility, which results in tools to be applied to improve the population’s quality of life in any city, aiming to prioritize public transport over individual, non-motorized vehicles over motorized ones, besides the improvement on displacement and road infrastructure. For that reason, evaluating these plans constitute an important stage, once it allows us to understand if the actions meet the goals proposed by the policies, if the financial resources are being well destined and applied and in what measure the non-effectiveness of the plan can generate problems to the city. Costa (2008) and Frey (2000) state that it is necessary to create evaluations for this took, as they aiming to guarantee the good development of the plan and to verify if it is necessary to adapt the program which is being developed, so that can may be taken actions. About the systems of urban mobility, different studies as Vasconcellos’s (2013) and Maricato’s (2011) point to the existence of crisis in most Brazilian cities, making the instruments for evaluation and monitoring even more relevant. Considering these elements, the goal of this study is to evaluate the actions towards urban mobility included in the Master Plan for Goiânia (Law number 171/2007) and the legislations which derive from it, paying special attention to the urban accessibility. To do so, we carried three kinds of research methodologies: bibliographical and documental, as well as the application of an evaluative method for public policies through the use of indicators by the confrontation of data between what was executed and the budget destined to these actions. The Indicators of Mobility have been usually applied on this kind of evaluation, because the measurement of their variables is easy to deal with, allowing agility on the decision making processes. The results indicate that there are no processes for monitoring and evaluating accessibility actions relative to the urban mobility system. Although it is possibly to verify that the budget destined to mobility has increased, the way the public and budgetary policies are applied between 2007 and 2017 do not allow us to analyze directly the correlation between physical and budgetary variables.